2012
DOI: 10.2134/jeq2010.0543
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Retention and Remobilization in Vegetated Buffer Strips: A Review

Abstract: Diff use pollution remains a major threat to surface waters due to eutrophication caused by phosphorus (P) transfer from agricultural land. Vegetated buff er strips (VBSs) are increasingly used to mitigate diff use P losses from agricultural land, having been shown to reduce particulate P transfer. However, retention of dissolved P (DP) has been lower, and in some cases VBSs have increased delivery to surface waters. Th e aims of this review were (i) to develop a conceptual model to enhance the understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 88 publications
(122 reference statements)
2
108
0
1
Order By: Relevance
“…Floodplains and riparian areas have the ability to retain, transform, and release nutrients, thereby influencing the water quality of the recipient water body (Hoffmann et al 2009;Roberts et al 2012). The sink and source function of riparian areas depends on the delivery pathway (surface runoff, drainage water, groundwater, or floodwater), the form of the delivered nutrient (particulate or dissolved), the specific biogeochemical conditions in the riparian area (e.g., soil humidity), the riparian vegetation, and the temperature (Fisher and Acreman 2004).…”
Section: Potential and Limitations Of Mitigation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Floodplains and riparian areas have the ability to retain, transform, and release nutrients, thereby influencing the water quality of the recipient water body (Hoffmann et al 2009;Roberts et al 2012). The sink and source function of riparian areas depends on the delivery pathway (surface runoff, drainage water, groundwater, or floodwater), the form of the delivered nutrient (particulate or dissolved), the specific biogeochemical conditions in the riparian area (e.g., soil humidity), the riparian vegetation, and the temperature (Fisher and Acreman 2004).…”
Section: Potential and Limitations Of Mitigation Measuresmentioning
confidence: 99%
“…Vegetated buffer strips are narrow, tillage-free, uncultivated border zones between agricultural areas and streams (Hoffmann et al 2009;Roberts et al 2012). While natural riparian zones vegetated with floodplain forests can also function as buffer zones, vegetated buffer strips are often optimized for nutrient removal as to vegetation type, width, and location, and they can be managed (Vought et al 1994;Mayer et al 2007).…”
Section: Potential and Limitations Of Mitigation Measuresmentioning
confidence: 99%
“…However, Suñer et al (2014) identified that the coarse fraction of the cultivated field had low levels of Pi as a consequence of the particulate organic matter decomposition and coarse mineral particle weathering. The reduction of Pi in coarse particle fractions in the buffer soil may be attributed to the assimilation by vegetation, transformation of Pi, leaching, and erosion (Roberts et al, 2012), which could have a positive influence on the function of the buffer to act as a sink for P. In the cropped soil, however, the accumulation of labile Pi in coarse particle fractions was considered to be more susceptible to lose P via leaching. Zheng et al (2003) observed that soil particles containing high amounts of extractable P have a higher P release potential.…”
Section: Land-use Effects On Inorganic Phosphorus Fractions In Particmentioning
confidence: 99%
“…The conversion of cropped soils to buffer strip can alter P stability. Roberts et al (2012) found that the buffer strip soils are enriched in soluble P compared with adjacent agricultural land. Schroeder and Kovar (2006) reported that levels of the iron (Fe)-P fractions were higher in the buffer area than crop field over a 20-year period.…”
Section: Introductionmentioning
confidence: 97%
“…Agricultural surface runoff (RO) is an important contributor to this contamination (Louchart et al, 2001). Grass buffer zones or vegetative filter strips (VFSs), are a typical environmental control practice to protect aquatic ecosystems from sediment, and agrichemicals from agricultural fields (Roberts et al, 2012). While VFSs are recommended in the USA and other regions, in Europe they are often mandatory along rivers due to their potential to limit surface pesticide runoff and aerial spray drift from entering adjacent surface water bodies (Asmussen et al, 1977;Rohde et al 1980;USDA-NRCS, 2000;Dosskey, 2001;Syversen and Bechmann, 2004;Poletika et al, 2009).…”
Section: Introductionmentioning
confidence: 99%